Is tobacco a risk factor for chronic pancreatitis and alcoholic cirrhosis?. Issue 11 (November 1991) - Bourliere, M; Barthet, M; Berthezene, P; Durbec, J P; Sarles, H
Abstract : In a case control study alcohol intake and tobacco use were assessed between 1975 and 1987 in 103 male patients suffering from alcoholic cirrhosis of the liver, in 145 patients with chronic pancreatitis, and in 264 control subjects. The patients with chronic pancreatitis were significantly younger than the patients with cirrhosis (mean (SD) age 41.92 (2.4) v 60.9 (11.6) years). Among the patients with chronic pancreatitis, 94% were both smokers and drinkers compared with 83% of patients with cirrhosis of the liver. The relative risks for each disease were calculated by conditional multiple logistic regression. Whereas daily intake of alcohol was a major risk factor for both cirrhosis of the liver and chronic pancreatitis, smoking was significantly related only to the risk of having chronic pancreatitis. Moreover, the mean age at onset of pancreatitis was lower among smokers.